Tinjuan Prosedur Operasional Media Sosial Direktorat Jenderal Pajak Dalam Rangka Edukasi Perpajakan - Nikolaus Pratama; Sony Hartono (JURNAL PAJAK INDONESIA, 2022)
Social media is one of the tax education channels by Directorate General of Taxation through Directorate of Extension, Services, and Public Relations. The dynamic nature of social media certainly requires Directorate of Extension, Services, and Public Relations to be able to formulate an appropriate operational procedure for each social media platform. The purpose of this study is to identify Directorate General of Taxation’s social media operational procedure in organizing tax education with its practices in reality, along with its obstacles, challenges, and strategies. The research result showed that operational procedures on several Directorate General of Taxation’s social media, such as Facebook, Instagram, Twitter, and YouTube, have been regulated in the latest regulation, KEP-701/PJ/2019. However, for other social media, such as TikTok, Spotify, and Linkedin, there has not been any specific regulation. In practice, Directorate General of Taxation’s social media still has some challenges and obstacles that need to be overcome. One of the challenges is negative feedbacks from the community, so Directorate General of Taxation must be able to manage the response properly.